2023
DOI: 10.1007/s10571-023-01399-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Hydrogen Sulfide Subchronic Treatment Against TBI-Induced Ferroptosis and Cognitive Deficits Mediated Through Wnt Signaling Pathway

Jie Chen,
Zhennan Chen,
Dongyu Yu
et al.

Abstract: Emerging evidence shows that targeting ferroptosis may be a potential therapeutic strategy for treating traumatic brain injury (TBI). Hydrogen sulfide (H2S) has been proven to play a neuroprotective role in TBI, but little is known about the effects of H2S on TBI-induced ferroptosis. In addition, it is reported that the Wnt signaling pathway can also actively regulate ferroptosis. However, whether H2S inhibits ferroptosis via the Wnt signaling pathway after TBI remains unclear. In this study, we first found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…2E ). Additionally, KEGG pathway analysis revealed that the 'MAPK signaling pathway' ( 51 , 52 ), 'Hippo signaling pathway' ( 53 ) and 'Wnt signaling pathway' ( 54 ) were enriched ( Fig. 2F ), suggesting that DElncRNAs are involved in ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…2E ). Additionally, KEGG pathway analysis revealed that the 'MAPK signaling pathway' ( 51 , 52 ), 'Hippo signaling pathway' ( 53 ) and 'Wnt signaling pathway' ( 54 ) were enriched ( Fig. 2F ), suggesting that DElncRNAs are involved in ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S has emerged as a prospective therapeutic agent, with anti-ferroptotic properties, enhancing brain function recovery following a TBI. Notably, the Wnt signaling pathway was significantly reduced after controlled cortical impact in mice, and its activation might be crucial in the neuroprotective effects associated with H 2 S in the context of TBIs [105]. Anacardic acid has also shown promise in alleviating neurological and behavioral cognitive impairments from TBIs via the dual effect of anti-ferroptosis and anti-inflammation [106].…”
Section: Antiferroptotic Strategies Enhance Neurorepair In Traumatic ...mentioning
confidence: 99%
“…Inhibition of ferroptosis may have been induced by H 2 S, perhaps via the Wnt/β-catenin pathway. [105] Weightdrop model…”
Section: Wnt3a and Gpx4mentioning
confidence: 99%